"I don't use a condom (with my regular partner) because I know that I'm faithful, but with everyone else I do": The cultural and socioeconomic determinants of sexual partner concurrency in young South Africans - Chris Kenyon; Andrew Boulle; Motasim Badri; Valerie Asselman (Taylor & Francis Group, 2010)
Finding ways to reduce the high rates of sexual partner concurrency is increasingly believed to be vital to controlling HIV spread in southern Africa. We describe the frequency and correlates of sexual partner concurrency in a representative sample of 3 324 young South Africans aged 14-25. Of the 2 468 individuals who were sexually active 21% had engaged in concurrent sexual partnerships. Multivariate analysis revealed that concurrency was more common with males, Africans, those who knew their partner had another partner, early age of sexual debut, four or more lifetime sexual partners, alcohol consumption, and self-perception of being at high risk for acquisition of HIV. If the respondent's partner knew his or her friends (termed high structural embeddedness) this was associated with a 52% reduction in concurrency rates. There are significant differences in both the rates of concurrency and the risk factors underpinning these in the different racial/ethnic groups. Analysis of these underlying determinants suggests that cultural rather than socioeconomic factors predominate, which has important implications for the design and targeting of prevention efforts.